(untitled) (Experimental biology, 2016)
The paper discusses the results of observations on semi-permanent environmental grounds (SPEG) key section №19. The key section №19 is located in the foothills of the desert-steppe zone of the South Kazakhstan Province, Central Trans-Ili district, sub sierozems light. Monitoring vegetation SPEG 55 showed that in the northwestern part of the plot area - 0.04 ha found saltwort-ephemeral with zhantakom community. Along with the plants, which occupy a leading position in the community, sporadically occur following: Ceratocarpus arenarius L., Stipa lessingianaTrin., Turgenia latifolia (L.) Hoffm., Diarthron vesiculosum (Fisch.et.Mey.) C.A.Mey., Serratulae rucifolia (L.) Boriss., Astragalus siversianus Pall.and other. Given the seasonal characteristics of plant communities and dynamics yields semi-permanent ecological site 55. The floristic list of surveys included 6 types. Role of edifikator’s belongs autumn wormwood. Subdominantes is the group of ephemera: tolstostolbikovaya sedge, bulbous bluegrass